Differences in fecal microbial metabolites and microbiota of children with autism spectrum disorders. (February 2018) - Kang, Dae-Wook; Ilhan, Zehra Esra; Isern, Nancy G.; Hoyt, David W.; Howsmon, Daniel P.; Shaffer, Michael; Lozupone, Catherine A.; Hahn, Juergen; Adams, James B.; Krajmalnik-Brown, Rosa
Abstract: Evidence supporting that gut problems are linked to ASD symptoms has been accumulating both in humans and animal models of ASD. Gut microbes and their metabolites may be linked not only to GI problems but also to ASD behavior symptoms. Despite this high interest, most previous studies have looked mainly at microbial structure, and studies on fecal metabolites are rare in the context of ASD. Thus, we aimed to detect fecal metabolites that may be present at significantly different concentrations between 21 children with ASD and 23 neurotypical children and to investigate its possible link to human gut microbiome. Using 1 H-NMR spectroscopy and 16S rRNA gene amplicon sequencing, we examined metabolite profiles and microbial compositions in fecal samples, respectively. Of the 59 metabolites detected, isopropanol concentrations were significantly higher in feces of children with ASD after multiple testing corrections. We also observed similar trends of fecal metabolites to previous studies; children with ASD have higher fecal p -cresol and possibly lower GABA concentrations. In addition, Fisher Discriminant Analysis (FDA) with leave-out-validation suggested that a group of metabolites-caprate, nicotinate, glutamine, thymine, and aspartate-may potentially function as a modest biomarker to separate ASD participants from the neurotypical group (78% sensitivity and 81% specificity). Consistent with our previous Arizona cohort study, we also confirmed lower gut microbial diversity and reduced relative abundances of phylotypes most closely related to Prevotella copri in children with ASD. After multiple testing corrections, we also learned that relative abundances of Feacalibacterium prausnitzii and Haemophilus parainfluenzae were lower in feces of children with ASD. Despite a relatively short list of fecal metabolites, the data in this study support that children with ASD have altered metabolite profiles in feces when compared with neurotypical children and warrant further investigation of metabolites in larger cohorts. Highlights: Isopropanol was higher in feces of children with ASD than neurotypical children. Feces of children with ASD have different abundance of possible neurotransmitters. Higher fecal p -cresol and possibly lower GABA concentrations for children with ASD. Fisher Discriminant Analysis suggests a group of 5 fecal metabolites as a biomarker. We confirmed lower microbial diversity and Prevotella in feces of children with ASD.